Groundwater Exploration For Agricultural Use Using Resistivity Imaging In Peninsular Malaysia - Muhammad , Kadri (2011)
Groundwater is a very important component of water resources. The demand of water increases with increasing population growth. Human activities and industries contribute to pollution of stream and river. In agriculture, efficiency of water use in irrigation in general is low. Irrigation efficiency is in the range of 40 to 50 percent because almost all of the irrigation systems are open systems designed to take advantage of flooding. In this study groundwater is suggested to supplement as an alternative source of water for irrigation. In Malaysia only less than 2% of the present water used is developed from groundwater. 2-D resistivity imaging is used in order to determine the existence of usable groundwater.